Geobacter Dominates the Inner Layers of a Stratified Biofilm on a Fluidized Anode During Brewery Wastewater Treatment - Tejedor-Sanz, Sara; Fernández-Labrador, Patricia; Hart, Steven; Torres, Cesar I.; Esteve-Núñez, Abraham (Frontiers in Microbiology, 2018)
In this study, we designed a microbial electrochemical fluidized bed reactor (ME-FBR), with an electroconductive anodic bed made of activated carbon particles for treating a brewery wastewater. Under a batch operating mode, acetate and propionate consumption rates were 13-fold and 2.4-fold higher, respectively, when the fluidized anode was polarized (0.2 V) with respect to open circuit conditions. Operating in a continuous mode, this system could effectively treat the brewery effluent at organic loading rates (OLR) over 1.7 kg m-3NRV d-1 and with removal efficiencies of 95±1.4% (hydraulic retention time of 1 day and an influent of 1.7 g-COD L-1). The coulombic efficiency values highly depended upon the OLR applied, and varied from a 56±15% to 10±1%. Fluorescence in situ hybridization (FISH) analysis revealed a relative high abundance of Geobacter species (ca. 20%), and clearly showed a natural microbial stratification. Interestingly, the Geobacter cluster was highly enriched in the innermost layers of the biofilm (thickness of 10 µm), which were in contact with the electroconductive particles of bed, whereas the rest of bacteria were located in the outermost layers. To our knowledge, this is the first time that such a clear microbial stratification has been observed on an anode-respiring biofilm. Our results revealed the relevant role of Geobacter in switching between the electrode and other microbial communities performing metabolic reactions in the outermost environment of the biofilm.